2017
DOI: 10.1097/md.0000000000006647
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical outcomes after drug-eluting stent implantation in diabetic versus nondiabetic patients in China

Abstract: Diabetes mellitus (DM) has been proved to be a predictor of adverse outcomes after percutaneous coronary intervention (PCI). Drug-eluting stents (DESs) could reduce the adverse events in DM patients. In this study, we aimed to analyze the clinical outcome after DES implantation in diabetic versus nondiabetic patients in China. Totally, 200 Chinese DM patients and 400 Chinese non-DM patients were enrolled in this retrospective study. Compared with non-DM patients, DM patients were more likely to have a higher i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Compared with Bundhun's study, we only focused on RCTs and long‐term studies. Furthermore, we removed a retrospective cohort study (Beneduce et al, 2020 ) that was used as an RCT study by Hassen et al During the two‐year follow‐up, Jiang et al ( 2017 ) found that patients with ITDM were more susceptible to stent thrombosis, TVR, and MACCE. Jain et al ( 2010 ) showed that insulin therapy was not statistically correlated with the increased tendency of stent thrombosis, although ITDM is a high‐risk factor for other cardiovascular adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with Bundhun's study, we only focused on RCTs and long‐term studies. Furthermore, we removed a retrospective cohort study (Beneduce et al, 2020 ) that was used as an RCT study by Hassen et al During the two‐year follow‐up, Jiang et al ( 2017 ) found that patients with ITDM were more susceptible to stent thrombosis, TVR, and MACCE. Jain et al ( 2010 ) showed that insulin therapy was not statistically correlated with the increased tendency of stent thrombosis, although ITDM is a high‐risk factor for other cardiovascular adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…The TLF rate for RESOLUTE Japan, included in the pooled analysis of Resolute studies, was also low with a rate of 5.6% at 4 years 13 . Reports of differences in thrombotic and thrombolytic status for Asian patients versus patients in Western countries have been postulated as reasons for differences in the underlying causes of thrombotic events 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…In a very recent retrospective study, Jiang et al presented data on apparent type 2 DM patients who were diagnosed by the following: an abnormal blood glucose level (≥126 mg/dL) after an overnight fast, an abnormal glycosylated hemoglobin test (≥6.5%), or an abnormal glucose tolerance test (2 hours, ≥200 mg/dL). 5 These patients type 2 DM were considered to have a disease predictive of adverse events after implantation of a DES. 5 In a meta-analysis by Zheng et al, it was found that increased blood levels of Hemoglobin A 1c were associated with increased major adverse cardiovascular events (MACEs) in patients with type 2 DM (these patients in the meta-analysis meet the criteria for type 2 DM as defined by the authors) following PCI.…”
mentioning
confidence: 99%
“…5 These patients type 2 DM were considered to have a disease predictive of adverse events after implantation of a DES. 5 In a meta-analysis by Zheng et al, it was found that increased blood levels of Hemoglobin A 1c were associated with increased major adverse cardiovascular events (MACEs) in patients with type 2 DM (these patients in the meta-analysis meet the criteria for type 2 DM as defined by the authors) following PCI. 6 Wang et al report an analysis of the impact of type 2 DM (type 2 DM criteria met by age) on a large cohort of patients (n ¼10 724) who underwent PCI at a single high-volume center in China.…”
mentioning
confidence: 99%